If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4 = x + 3 * 2 Reorder the terms: -4 + 5x = x + 3 * 2 Multiply 3 * 2 -4 + 5x = x + 6 Reorder the terms: -4 + 5x = 6 + x Solving -4 + 5x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 5x + -1x = 6 + x + -1x Combine like terms: 5x + -1x = 4x -4 + 4x = 6 + x + -1x Combine like terms: x + -1x = 0 -4 + 4x = 6 + 0 -4 + 4x = 6 Add '4' to each side of the equation. -4 + 4 + 4x = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 6 + 4 4x = 6 + 4 Combine like terms: 6 + 4 = 10 4x = 10 Divide each side by '4'. x = 2.5 Simplifying x = 2.5
| 5[2-g]=0 | | 14=3m+5 | | 5+6=4+Y | | 10[1-2y]=-5[2y-1] | | -3sin(t)+2cos(t)=0 | | 3(3+2x)-4x=59-3x | | 15z-2=(2z+3) | | 3x-(12x-x)=5+2(x-1)-1 | | 3y+5y+2y= | | 6r-6=72-6 | | 5n-30=20 | | 3x-(12-x)=5+2(x+1)-1 | | 5y=11x-7 | | 3(x+5)-2=6x-3(-4+x) | | -8x+3=25 | | 5y=11x+7 | | LNx=-1.6 | | Log(8x-7)/log(x) | | -6f+13=-9z+24 | | 9(5+x)=8(x-4) | | 5+2X=14-4N | | 4y-13=43 | | -8b/5=-1 | | 4x-38=9x-3 | | 5x+39=154 | | 6+65x=52x+18 | | x-5x^(1/2)-6=0 | | 2.6(x-0.8)=9 | | 7(y+6)=3+6y | | 6+65x=52+18 | | x^2+21x+30=9x+3 | | 112x+6=5x |